The Effect of Crude Oil Price Shocks on Indonesia Stock Market Performance - Darmawan, Indra; Siregar, Hermanto; Hakim, Dedi Budiman; Manurung, Adler Haymans (LPPM Universitas Terbuka, 2020)
The primary purpose of this study is to investigate the effects of crude oil price shocks on Indonesia stock market performance, represented by the composite index (IHSG). We used a vector error correction model (VECM) approach to observe the relationship between Brent crude oil price (BPO) and the seven stock market indices, including IHSG, and the relationship between IHSG and the six global stock market indices. Findings. The results show that the Brent crude oil prices cointegrated to the seven stock market indices, including IHSG, and IHSG cointegrated to the six global stock market indices. This finding proves that crude oil price shocks affect the Indonesia stock market performance directly through the co-integration mechanism between the crude oil price and IHSG and indirectly transmitted through the co-integration mechanism between IHSG and the global stock market indices.